Exposure to the herbicide glyphosate leads to inappropriate threat responses and alters gut microbial composition - Cáceres-Chacón, Mauricio; Martínez-Guzmán, Osmarie; Haddock-Martínez, Héctor A.; Figueroa-Pérez, Alexdiel; Rodríguez-Rosado, Sian; Suárez-Pérez, Jaleniz; Ramos-Sánchez, Raúl Y.; Godoy-Vitorino, Filipa; Sierra-Mercado, Demetrio (Frontiers in Toxicology, 2025)
BackgroundExposure to the herbicide glyphosate may contribute to anxiety-related disorders. The mechanisms by which this occurs may involve effects on brain regions or alterations of gut microbiota implicated in emotions. Pre-clinical studies use unusually high doses to which humans may not normally be exposed. The effects of glyphosate on anxiety at doses considered safe are largely unexplored.MethodsAdult male rats were administered glyphosate at a dose considered safe for 16 weeks. After 4 and 10 weeks, anxiety-like behaviors were tested in the open field and elevated plus maze, respectively. After 14 weeks, rats interacted with a novel neutral object, followed by a naïve rat of the same age and sex as a conspecific. Lastly, after 16 weeks, rats underwent fear conditioning, and freezing was quantified. Upon completion of the experiments, cellular activity was assessed using immunohistochemistry in brain regions implicated in anxiety and fear. Fecal pellets were collected to extract DNA and perform 16S rRNA community analyses.ResultsGlyphosate increases anxiety in the elevated plus maze after 10 weeks. Moreover, glyphosate decreases interaction to a novel object, but not to the conspecific, after 14 weeks. Furthermore, freezing increases to a novel neutral tone, but not a conditioned tone, after 16 weeks. Behavioral changes correspond to increases in cellular activity in the bed nucleus of the stria terminalis. Furthermore, we observed that glyphosate induces changes in the gut microbiota leading to a decrease in Lactobacillus species.ConclusionGlyphosate increases threat interpretation and alters cellular activity in brain regions implicated in promoting anxiety. Also, glyphosate induces gut dysbiosis and reduces the abundance of Lactobacillus, bacteria that play a role in the production of serotonin, which may further exacerbate the anxiogenic effect of glyphosate.